A comparative study of Al-Makki and Al-ghazali on spiritual dimension of Raja’ (HOPE) approach in treating drug addicts - Nor Fatin Syuhaidah Nayan; Rozeeda Kadri; Nor Iman Nabila Abu Bakar; Siti Hanisah Sabri (Global Academic Excellence, 2024)
Drug abuse is a global alarming concern that affects the world community, including Malaysia with the significant numbers increasing day by days. Drugs were scientifically proven as a damaging substance to brain functionality, which controls social behaviour, reward systems, and human motivational systems. Drug dependency has impacted severely for individuals and society. However, drug addicts are constantly looking for drugs, knowing the fact that the substances are affecting them for a prolonged period. As a response, drugs have been banned in Islam considering their impact on humanity. Thus, several interventions were initiated as a preventative mechanism to address the issue properly. Several types of approaches have been carried including pharmacological, psychological, and psychodynamic treatments to overcome the problem of drug abuse. Therefore, this study seeks to find an alternative treatment for drug addiction based on the religiosity and spirituality approach of the Islamic dimension. This study also intends to evaluate the differences between Al-Makki's views regarding raja' as compared to al-Ghazali. This study is qualitative in nature and therefore, it depends much on in-depth textual analysis. The data was analytically studied from the relevant works of al-Ghazali and Abu Talib al-Makki and later were compared to develop the concept of raja' as suggested by Islam. The finding shows that both figures have extensively discussed the prevalent concept of raja’ as a salutary employment of hope of the soul. It is also suggested that al-Ghazali' ideas was highly influenced by al-Makki, however, he strategizes the concept in an extensive arrangement. Al-Makki emphasizes raja' or hope as the powerful desire of a human being upon requesting something from Allah. The fundamental elements of hope, especially inner meaning, and inner action, can be regarded as a spiritual model for a drug addict considering these spiritual insights are still applicable in modern Muslim society. Hope is believed to be spiritual motivating factors for them to stop the addiction with the help of medication and support from surrounding. This implies that spirituality dimension is a complimentary to a holistic treatment of most illness especially in dealing with addiction. Thus, is it suggested for a structured models to be made based on the concept of raja’ for future study.